2007
DOI: 10.1159/000104764
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Periocular Sebaceous Gland Carcinoma

Abstract: Background: We analyzed the clinicopathological features and prognosis in patients with periocular sebaceous gland carcinoma. Methods: Retrospectively, we studied the records of 24 cases of sebaceous gland carcinoma treated in our clinic between 1999 and 2004. The reviewed data included demographic information, initial clinical and histopathological diagnosis, anatomic tumor location, details of treatment, tumor involvement of resection margin, and outcomes such as local recurrence, distant metastasis and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…In contrast, 94% of our patients presented with a solitary mass or nodule, and 29% of our cases were misdiagnosed as a chalazion, compared with just 5% as blepharoconjunctivitis. This difference in presentation between Caucasian and Asian patients is also reflected in the literature, with chalazion being the most commonly reported misdiagnosis of sebaceous carcinoma from Japanese and Korean studies 12 14. This possible difference in clinical presentation may also be a factor in the lower rate of clinical misdiagnosis in Asian populations as compared with Caucasian ones.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In contrast, 94% of our patients presented with a solitary mass or nodule, and 29% of our cases were misdiagnosed as a chalazion, compared with just 5% as blepharoconjunctivitis. This difference in presentation between Caucasian and Asian patients is also reflected in the literature, with chalazion being the most commonly reported misdiagnosis of sebaceous carcinoma from Japanese and Korean studies 12 14. This possible difference in clinical presentation may also be a factor in the lower rate of clinical misdiagnosis in Asian populations as compared with Caucasian ones.…”
Section: Discussionmentioning
confidence: 81%
“…However, we found much lower rates, with just 21% of our cases demonstrating pagetoid spread histologically. Yoon et al 14 reported even fewer cases of pagetoid spread within their Korean series, which occurred in only 8.3% of patients. Chao et al also demonstrated differing clinical features of sebaceous carcinoma depending on the presence of intraepithelial spread, with 72% of patients with pagetoid spread presenting with diffuse eyelid thickening and 43% of patients without pagetoid spread presenting with a distinct mass 16.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the mortality rate of this carcinoma is relatively low, local invasion and metastasis to regional lymph nodes or distant organs occasionally occur in aggressive cases (Shields et al 2005;Song et al 2008). The recurrence rate of SbGC has been reported to be up to 10-25 % (Shields et al 2004;Song et al 2008;Yoon et al 2007). The standard frontline treatment of eyelid SbGC is either wide excision or Mohs micrographic surgery; however, the tendency for multicentricity or pagetoid spread remains the main obstacle preventing its complete removal.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy may be given to those patients who refuse surgery. Features of poor prognosis include orbital invasion, poor differentiation, tumour diameter of more than 10 mm and lacrimal gland involvement 22 23. Tumours of the lower eye lid have been associated with better prognosis than those affecting the lower lid 24…”
Section: Discussionmentioning
confidence: 99%